2006
DOI: 10.1111/j.1542-474x.2006.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented Left Sided QRS in Absence of Bundle Branch Block: Sign of Left Ventricular Aneurysm

Abstract: The sensitivity of fragmented QRS in left precordial leads for LVA was only 50%, whereas the specificity was 94.5%. It has a relatively low to moderate positive predictive value and high negative predictive value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 30 publications
0
38
0
2
Order By: Relevance
“…21 The study also confirmed the prior angiographic correlation of the RSRЈ pattern with MI scar. 10,11 Autopsies of patients with MI and left ventricular aneurysm have also confirmed significant myocardial necrosis, with "islands" of viable myocardial tissue interspersed in abundant fibrous tissue. The islands of chronically ischemic myocar- dium display slow activation as a result of partially depolarized and depressed action potential upstroke velocities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The study also confirmed the prior angiographic correlation of the RSRЈ pattern with MI scar. 10,11 Autopsies of patients with MI and left ventricular aneurysm have also confirmed significant myocardial necrosis, with "islands" of viable myocardial tissue interspersed in abundant fibrous tissue. The islands of chronically ischemic myocar- dium display slow activation as a result of partially depolarized and depressed action potential upstroke velocities.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 We have also demonstrated that the presence of an RSRЈ pattern, without evidence of a typical bundle-branch block (QRS Յ120 ms), is associated with ventricular aneurysm by left ventriculography. 10,11 In addition, during that study, we anecdotally found that the RSRЈ pattern was not limited to the precordial leads, and when present in inferior leads, it was often associated with inferior wall motion abnormalities. This novel observation led us to evaluate this ECG sign of a prior MI in patients referred for cardiac stress testing by nuclear perfusion analysis.…”
Section: Clinical Perspective P 2501mentioning
confidence: 99%
“…In previous studies using Gadolinium delayed enhancement on cardiac magnetic resonance imaging to determine myocardial structure, fQRS related to extensive myocardial scar (11,12). Prior studies demonstrated fQRS to be a marker of a prior MI, defined by regional perfusion abnormalities, which has a substantially higher sensitivity and negative predictive value compared to the Q wave (6,29). Regional fQRS patterns denote the presence of a greater corresponding focal regional myocardial scar on stress myocardial perfusion imaging (30).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the combination of Q wave and fQRS improved the sensitivity (91.4%), specificity (89%), and negative predictable value (92.4%) for detection of scared myocardium [27].…”
Section: Discussionmentioning
confidence: 99%